Optimized holographic pattern for diffused infrared wireless communication - Ramalingam Ramya (2008)
This thesis consists of 2 parts. Wireless communications offer a viable alternative to radio frequency (RF) communication for indoor use and other applications where high performance are needed. These systems use infrared technology (IR), which has significant advantages over RF. The most important advantages offered by infrared over radio are the availability of a virtually unlimited, unregulated spectrum, and the fact that infrared radiation does not pass through walls or other opaque barriers. Diffused infrared transmission is one of the preferred techniques used in indoor wireless communication. The project explores in the area of holographic diffuser for infrared wireless communication. The objective of the project is to reduce the zero order intensity or the central spot in holographic diffuser, and to get a better distribution of light. The hologram act as a beam splitter dividing the original laser beam from the transmitter into multiple beams. The hologram was fabricated using photolithography, followed by reactive ion etching on quartz substrate.